Analisis Pengaruh Keterampilan Kerja dan Perilaku Karyawan Terhadap Kinerja Karyawan dengan Variabel Peran Manajerial sebagai Moderasi - Dwi Mei Ristanti; Taufik Rachmad Fauzy (Jurnal SENOPATI : Sustainability, Ergonomics, Optimization, and Application of Industrial Engineering, 2022)
The aim of this research is as to determine the effect of work skills, employee behavior, managerial on employee performance, determine the effect of employee behavior on employee performance and the results of the comparison between, as direct and indirect effects.The method used is the SEM (Structural Equation Modeling) method with variable analysis using the CFA (Confirmatory Factor Analysis) method. The results of the study indicate that the skill variable has an influence of 0.053 on employee performance, the employee behavior variable has an influence of 0.212 on employee performance, the managerial variable has an influence of 0.044 on employee performance, the skills variable has an influence of 0.023 on employee performance through managerial roles, and employee behavior variable has an effect of 0.127 on employee performance through managerial roles.Keywords: work skills, employee behavior, managerial roles, performance, variables